How useful is the current species recognition concept for the determination of true morels? Insights from the Czech Republic - Petrželová, Irena; Sochor, Michal (MycoKeys, 2019)
The phylogentic diversity of the genus Morchella has only been sporadically studied in Central Europe. In this study, a molecular taxonomic revision of the Morchella species of the Czech Republic was performed using available fungarium specimens, fresh collections, and axenic cultures. Molecular phylogenetic analyses based on either ITS or five-locus (ITS, LSU, RPB1, RPB2, and EF-1α) sequencing and the application of principles of the genealogical concordance phylogenetic species recognition (GCPSR) have revealed the occurrence of 11 phylogenetic species in the region, but only six of them could be assigned unequivocally to the previously published phylospecies: Mel-3 (M.semilibera), Mel-10 (M.importuna), Mel-19 (M.eohespera), Mes-4 (M.americana), Mes-5 and Mes-8 (M.esculenta). One lineage was identified as a new phylospecies and is designated as Mel-39. Four lineages grouped together with two or more previously published phylospecies: Mel-13/26 (M.deliciosa), Mel-15/16 (M.angusticeps / M.eximioides), Mel-20/34 (M.purpurascens), and Mel-23/24/31/32 (M.pulchella). Our phylogenetic analyses and literature review shed light on the pitfalls of current molecular taxonomy of morels and highlight the ambiguities of present species recognition concepts. The main source of the problems seems to be rooted in the application of different methods (multigene vs single-gene sequencing, phenotypic determination) and approaches (monophyly vs paraphyly, the application or not of GCPSR, degree of differentiation between accepted species, etc.) by various authors for the delimitation of new phylospecies. Therefore, we propose five criteria for distinguishing new phylospecies in the genus Morchella based on molecular data, and recommend a more conservative approach in species delimitation.
Keywords: Morchella; phylospecies; Mel-39; multigene analysis; GCPSR; species concept